Identificação de não conformidades no leite humano processado em um banco de leite de referência em Belém-Pa - MOREIRA, Alana Galvão (2023)
This is a retrospective quantitative research on the identification of nonconformities of processed human milk (LHP). Its objectives were to describe the main types of losses of Human Milk (LH) by analysis during the process, determine the volume of lost milk between the period of the data collection of the research and identify the LH losses of the external collection according to the neighborhood. He use of secondary data provided by the Human Milk Bank of the Santa Casa de Misericórdia Foundation of Pará (FSCMP) was used for this study, which is duly authorized by the maternity research management. The analysis that presented the highest value of LH discard due to noncompliance was soil contamination, showing a percentage in the months of January, February and March, 51.2%, 51.6% and 34.4%, followed by the second greater loss than the verification of the glass packaging of the milk donation, totaling percentage values in the months of January to March of 25%, 40.6% and 12.3%. In relation to the determination of the volume of lost Milk, a similar and high loss, equivalent in the first months of the year 2019, of 110,350 ml of Human Milk not considered for consumption was analyzed during the months of the research. The district of Belém do Pará, which presented the largest milk discharge due to noncompliance with the quality standards established by the Brazilian Network of Human Milk Bank and the National Agency of Sanitary Surveillance (ANVISA), was the Cabanagem neighborhood, followed by the neighborhoods of sacramenta, Umarizal and Barreiro. These data contribute to the accomplishment of an action research carried out by members of the research group "Nutritional Aspects in Health", aiming the direction of solutions and greater attention to the districts mentioned, in order to reduce the losses of this complete and sufficient food to guarantee the growth and healthy development of babies.